2013
DOI: 10.4236/jilsa.2013.54024
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Metro Door System Based on FMECA

Abstract: The metro door system is one of the high failure rate subsystems of metro trains. The Failure Mode, Effects and Criticality Analysis (FMECA) method is applied to analyze the reliability of metro door system in this paper. Firstly, failure components of the door are statistically analyzed, and the major failure components are determined. Secondly, failures are classified according to their impacts on operation, and methods of calculating failure mode criticality and the related coefficients are illustrated. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Wang L et al [37] proposed an extended FMECA method for optimizing equipment maintenance, using metro vehicles as an example, and demonstrated that the proposed method could quantitatively measure reliability, availability, and maintenance cost risk. Cheng X et al [6] applied FMECA to the reliability analysis of the subway sliding plug door system. They optimized the design and maintenance of the door system based on the analysis results.…”
Section: Eksploatacja I Niezawodnosc -Maintenance and Reliabilitymentioning
confidence: 99%
“…Wang L et al [37] proposed an extended FMECA method for optimizing equipment maintenance, using metro vehicles as an example, and demonstrated that the proposed method could quantitatively measure reliability, availability, and maintenance cost risk. Cheng X et al [6] applied FMECA to the reliability analysis of the subway sliding plug door system. They optimized the design and maintenance of the door system based on the analysis results.…”
Section: Eksploatacja I Niezawodnosc -Maintenance and Reliabilitymentioning
confidence: 99%
“…As presented in [10] these include, for example, ETA (Event Tree Analysis); FTA (Fault Tree Analysis); FMECA (Failure Mode Effect & Criticality Analysis). These and others methods are among others used to conduct process of identification of the weakest components of rail vehicle [39] (including metro vehicles [30]), evaluate different components of rail vehicles such as bogies [26,29], running gear [34], heating, ventilation and air conditioning system (HVAC) [2], doors [3,13] and others. It is worth noting that the list of methods by which the risk may be assessed is not finite, it is the railway entity that conducts it that makes the choice.…”
Section: List Of Safety Critical Componentsmentioning
confidence: 99%
“…Despite rigorous maintenance schedules, doors and brakes continue causing incidents which drive undesirable consequences, and in addition, the causes of failure cannot always be identified. Doors, in particular, have been a subject of research to find better ways to identify and prevent failure (Dinmohammadi et al, 2016;Van der Gucht et al, 2011;Shuai et al, 2014;Cheng et al, 2013). A case study conducted in UK reported that the cause of failure could not be identified for 42% of a total of 205 incidents with the passenger doors (Dinmohammadi et al, 2016).…”
Section: Performance Of Rail Passenger Doors and Brakes Systemsmentioning
confidence: 99%